İstanbul’da bazı SSK kurumlarında ve İstanbul Üniversitesi Diş Hekimliği Fakültesi’nde çalışan diş hekimlerinin iş tatminlerinin değerlendirilmesi - Gezgin, Yeşim (My University, 1999)
This research of descriptive nature, has been conducted during the period between May and October 1999 in Istanbul over 120 people in total, 60 of which are the dentists employed under Social Security Institution and the remainder are the dentists working at Istanbul University, Faculty of Dentistry. The object of this research is to measure the job-satisfaction levels of the dentists working at these institutions, to determine some of their professional and socio-demographical characteristics, to put forward the differences between these two institutions with respect to job-satisfaction and to contribute to the process of taking measures by the administrators in order to increase the level of job-satisfaction. The data were collected by the researcher through application of an questionnaire form prepared by the researcher, under observation, In the process of data-collection, the job-satisfaction scale of Minnesota Satisfaction Questionnaire (MSQ) was used. As a result of evaluation of this study, it was found that the dentists have job- satisfaction of average level in both institutions and those working at the university are more satisfied with their jobs than those employed by SSK at a significant degree. With both institutions, the variable scored with the minimum satisfaction point by the dentists are; wage, working conditions, promotion, while the highest scored variables are moral values, social service, friendship and position. As a result of these findings, it was proposed that the job-satisfaction researches should be conducted over the dentists more extensively, the working environment and conditions of the dentists should be improved, the chambers of dentists should promote such researches and the administrators should take necessary measures.
Keywords: DİŞ HEKİMLİĞİ-İŞ TATMİNİ; PERSONEL YÖNETİMİ-SAĞLIK SEKTÖRÜ